Non‐native species threaten the biotic integrity of the largest remnant Pacific Northwest Bunchgrass prairie in the United States. Issue 1 (20th December 2019) - Endress, Bryan A.; Averett, Joshua P.; Naylor, Bridgett J.; Morris, Lesley R.; Taylor, Robert V.
Abstract: Questions: The Pacific Northwest Bunchgrass ecosystem is one of the most endangered in the United States, yet community‐level patterns of non‐native plant distribution and abundance remain largely unexplored. To address this information gap, we asked the following questions: What are the distinct plant communities within Zumwalt Prairie Preserve? What are the most widespread and abundant non‐native species and how does non‐native species composition and dominance vary across plant communities? How do historic land use, biotic and environmental factors influence plant community composition, particularly in terms of non‐native species abundance and dominance? Location: Zumwalt Prairie Preserve, Wallowa County, Oregon, USA. Methods: We sampled 123 plots using point‐intercept methods within a stratified random sampling approach. We analyzed community variation using cluster analysis, indicator species analysis, and non‐metric multidimensional scaling, and related composition and non‐native plant abundance to historical land use, biotic and environmental variables using joint plots, linear regression, and non‐parametric multiplicative regression. Results: While native perennial grasses were the most abundant species, non‐native species accounted for 27% of species encountered and four of the ten most abundant species were non‐native annual grasses (e.g., Ventenata dubia ) or non‐native perennial grasses (e.g., Poa pratensis ). Abundance patterns of non‐native perennial grasses differed markedly from those of non‐native annual grasses; non‐native perennial grasses were concentrated in old fields, while non‐native annual grasses were abundant in moisture‐limited uncultivated sites. Conclusions: Despite its protected status, non‐native plant species pose a serious threat to the biotic integrity of the Preserve, with unknown consequences to ecosystem dynamics and function. Moreover, patterns of non‐native abundance vary considerably, with different species responding individually to land‐use, environmental, and biotic gradients. An improved understanding of the relationship between non‐native species distributions and historical, environmental, and biotic factors can help in the development of ecologically appropriate, cost‐effective strategies for the conservation and restoration of this unique landscape. Abstract : Plant composition was evaluated in the largest remnant Pacific Northwest Bunchgrass ecosystem in the US and we related composition to land‐use, biotic, and environmental factors. Non‐native plants accounted for 27% of species, and four of the ten most abundant species were non‐native. Despite its protected status, non‐native species pose a serious threat to the biotic integrity of remaining grasslands.